SISTEM PENDETEKSI KEBOCORAN TABUNG GAS ELPIJI (LPG) BERBASIS NODEMCU DAN TELEGRAM - Alamsyah, Nur; Nurlaela Safitri (FKOM UNIKU, 2023)
The increasing population level of society makes the level of public consumption of natural resources also increase, in this case the increase occurs in the use of LPG (Liquefied Petroleum Gas) fuel. With the increasing use of LPG fuel, it is possible for fires to occur caused by LPG gas leaks. However, not all LPG gas cylinder providers provide additional safety systems on the LPG cylinders they sell. So an LPG gas leak detection device and a system that can provide information in the event of an LPG cylinder leak are needed. For this reason, an LPG gas leak detection device is made using a Telegram notification system, and an MQ-2 Sensor that can detect LPG gas and provide an alarm sound and LED indicator and LCD display display. so that it can provide a warning if the owner of the LPG cylinder is outside the house. All of these components are controlled using a Nodemcu Microcontroller. This tool has the advantage of being easy to use and compatible with all Telegram-based communication devices.